2019
DOI: 10.1248/bpb.b19-00050
|View full text |Cite
|
Sign up to set email alerts
|

Qiliqiangxin Attenuates Oxidative Stress-Induced Mitochondrion-Dependent Apoptosis in Cardiomyocytes <i>via</i> PI3K/AKT/GSK3β Signaling Pathway

Abstract: Qiliqiangxin capsule (QLQX) is a well-known traditional Chinese medicine that exhibits cardioprotective effects in heart failure patients. However, it remains unclear whether and by which mechanism QLQX attenuates oxidative stress-induced mitochondria-dependent myocardial apoptosis. In vivo, Sprague Dawley (SD) rats received left anterior descending coronary artery ligation for 4 weeks to establish a model of heart failure after acute myocardial infarction, and then were treated with QLQX for another 4 weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…It is one of the more extensively investigated signaling pathways in clinical research. According to numerous studies, this pathway is activated following I/R injury, and effectively reduces the area of myocardial infarction, which is also the target of a number of biological molecules and drugs (14,33,34). Components of this signaling pathway were analyzed at the protein and mRNA levels to determine whether the protective effect of OMT on cardiomyocytes subjected to H/R injury was associated with this signaling pathway and to verify the pathway upstream of the Nrf2/HO-1 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the more extensively investigated signaling pathways in clinical research. According to numerous studies, this pathway is activated following I/R injury, and effectively reduces the area of myocardial infarction, which is also the target of a number of biological molecules and drugs (14,33,34). Components of this signaling pathway were analyzed at the protein and mRNA levels to determine whether the protective effect of OMT on cardiomyocytes subjected to H/R injury was associated with this signaling pathway and to verify the pathway upstream of the Nrf2/HO-1 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The 8-Gin L and 8-Gin H groups were treated with 8-Gin [10 and 20 mg/kg/d, intraperitoneally (i.p. ), respectively] ( Nieuwenhuiset al, 2010 ; Zhao et al, 2019 ), and then subcutaneously injected with ISO (10 mg/kg/d). The CAP group was treated with CAP (45 mg/kg/d, i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…Due to the different chain-lengths in its molecular structure, gingerol can be subdivided into 6-, 8-and 10-gingerols (6-, 8-, and 10-Gin) (Wymann et al, 2003). Previous research has confirmed that 8-Gin (Figure 1) has various pharmacological properties, including anti-inflammatory and anti-oxidative capacities, immunosuppressive activity, and cardiotonic action (Li et al, 2018b;Takino et al, 2019;Zhao et al, 2019). However, the cardioprotective effects of 8-Gin against isoproterenol (ISO)induced MF have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In rat primary cardiac microvascular endothelial cells (CMECs) subjected to hypoxia, QLQX was found to improve glucose utilization and protect CMECs against hypoxia-induced injury by promoting hypoxia-inducible factor 1-alpha (HIF-1a)-dependent glycolysis (Wang et al, 2018a). Zhao et al (2019) conducted the myocardial infarction surgery in male SD rats fed with (0.25, 0.5, and 1.0 g/kg/day) QLQX. 4 weeks after myocardial infarction, QLQX treatment protected cardiac function, ameliorated mitochondria-dependent apoptosis, and enhanced p-AKT and p-GSK3b expression.…”
Section: Qiliqiangxin Capsulementioning
confidence: 99%